Building Form berdasarkan Sejarah Kawasan Bangunan pada Jalan Basuki Rahmat Malang - Ridjal, Abraham Mohammad; Antariksa, Antariksa; Suryasari, Noviani; Santoso, Joko Triwinarto (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2016)
Human civilization had been through along with the evidence of history. The city of Malang has its own history which been proved by its buildings as the eyewitnesses. As a part of Indonesian History, Malang contributed to colonialism era in which colored this nation efforts during the independence through its buildings which became the evidence of what happened. The existence of these buildings were important for the record of history, not just political stories but also how did people acted in it. Ignorance of these could erase the history of Malang, in which could stop the transfer information about what did Malang. In this case identified and re-constructed history of Malang is needed to re-built its identity. Through this agenda by historical-description hoped Malang Identity could be found and the building form could re-arranged through its character. If this action done, development of Malang city would be synergy with its own history and identity.Keywords: conservation, history, colonialism